1987
DOI: 10.1121/1.2024621
|View full text |Cite
|
Sign up to set email alerts
|

Perception of vowel nasalization in VC contexts: A cross-language study

Abstract: A series of stimuli ranging between [tΛtΛ], [tΛ̄tΛ], and [tΛntΛ] were synthesized by systematically manipulating (1) the duration of nasalization in the vowel [Λ], (2) the amount of nasalization in the vowel, and (3) the duration of the nasal murmur following the vowel. The stimuli were presented to native speakers of Portuguese, English, and French, which differ with respect to the occurrence of nasal vowels in their phonological systems. The listeners were asked to judge, for each stimulus, (1) the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Nasalization is primarily a͒ characterized by a decrease in the amplitude of the first formant ͑F1͒. Perceptual experiments of synthetic stimuli showed that F1 amplitude lowered by 6 -8 dB is necessary to achieve a significant level of nasality perception ͑House and Stevens, 1956;Stevens et al, 1988͒. The reduced F1 amplitude is associated with an increase in formant bandwidths and upward shifts in formant frequencies.…”
Section: Introductionmentioning
confidence: 97%
“…Nasalization is primarily a͒ characterized by a decrease in the amplitude of the first formant ͑F1͒. Perceptual experiments of synthetic stimuli showed that F1 amplitude lowered by 6 -8 dB is necessary to achieve a significant level of nasality perception ͑House and Stevens, 1956;Stevens et al, 1988͒. The reduced F1 amplitude is associated with an increase in formant bandwidths and upward shifts in formant frequencies.…”
Section: Introductionmentioning
confidence: 97%
“…It is possible that the nasal and oral sounds identifications may be similar to many languages, but the natural discrimination and judgments appear to differ depending on the spoken language. Indeed, Stevens et al's [33] stated that nasal-ization patterns across Portuguese, French and English speakers are different. These differences appear to be consistent with the acoustic characteristics of nasalization of French, Portuguese and English speakers [12,41].…”
Section: Discussionmentioning
confidence: 99%
“…Duration: Previous studies in French nasality have indicated that increased vowel duration (V.Dur) can be a quality of oronasal vowels when compared against similar oral vowels. Stevens et al (1987) found duration to be a salient feature in their perception tests. Delvaux et al (2012) found the duration of oronasal vowels in NMF to be even longer than the oronasal vowels in Southern French; both were longer than their oral counterparts.…”
Section: Acoustic Measuresmentioning
confidence: 95%